Role of Military From Counter Insurgency to Peace Building: Paradigm Shift in the Sri Lankan Nation-Stateʼs Security - Rukshan, D.G. Rajitha Nilaksha (European Scientific Journal, ESJ, 2021)
Historically, Sri Lanka (Ceylon) used to be considered as one of the more stable and secure countries in the South Asian region. In the years after independence it gradually dawned on the government that maintaining national security was a crucial and most challenging contemporary issue faced by the country. At the global level, the role of the Military was understood as being vital for ensuring the safety, security and dignity of the nation-state. And, when national security is threatened on any ground, the military is expected to play a key role in safeguarding it. However, after the military victory was won by defeating the Liberation Tigers of Tamil Eelam (LTTE) in Sri Lanka in 2009 it was expected that a deep sense of peace and tranquility would be restored in the country. Contrary to this expectation, Sri Lankan national security was breached very badly, leadimg to an unstable situation as a result of a series of bomb blasts set off by certain extremist elements on the 21st of April 2019. In this backdrop, it would be a timely exercise to explore and analyze the Sri Lankan nation stateʼs security, peace building initiatives, and the role of the military. Taking this a step further, this study sought to analyze the role played by the military in the post-conflict peace building process as well. The study used qualitative methodology to conduct the investigation. Secondary data sources including books, articles and official reports were utilized to collect information for this study. This research found that in Sri Lanka the military was actively engaged in maintaining national security by using its soft and hard power as appropriate. This Study also found that lack of a coherent National Security Policy in Sri Lanka has been a key problem that needs to be addressed and corrected soon to ensure the safety and security of the country.